2023
DOI: 10.1002/fsn3.3327
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable‐enriched bread: Pilot and feasibility study of measurement of changes in skin carotenoid concentrations by reflection spectroscopy as a biomarker of vegetable intake

Abstract: Globally, bread is a staple food and thus a promising vehicle for the delivery of nutrients from vegetables including carotenoids. The aim of this pilot/feasibility, pre–post experimental study was to measure skin (Veggie Meter™) and plasma carotenoid concentrations 1 week before (week −1), immediately prior to (week 0), and after (week 2) 14 days of daily consumption of 200 g pumpkin‐ and sweetcorn‐enriched bread (VB). At each measurement point, total vegetable and fruit intake and specific carotenoid‐rich fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The vegetable processing industry produces more than a million tons of vegetable by‐products as garbage, each year which is a potential source of bioactive ingredients (Galali et al, 2020 ; Rafiuddin et al, 2019 , 2021 ). Studies have shown that there is a huge potential of utilizing by‐products from vegetable sources for developing food products (Amoah et al, 2023 ; San José et al, 2018 ; Tamasi et al, 2019 ). Cauliflower by‐products (CBP) are intended to hold a large share in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The vegetable processing industry produces more than a million tons of vegetable by‐products as garbage, each year which is a potential source of bioactive ingredients (Galali et al, 2020 ; Rafiuddin et al, 2019 , 2021 ). Studies have shown that there is a huge potential of utilizing by‐products from vegetable sources for developing food products (Amoah et al, 2023 ; San José et al, 2018 ; Tamasi et al, 2019 ). Cauliflower by‐products (CBP) are intended to hold a large share in this regard.…”
Section: Introductionmentioning
confidence: 99%